Efeito de subtrações da proteína do látex da Calotropis procera na mucosite oral induzida por 5-fluorouracil - Freitas, Ana Paula Fragoso de (2016)
Oral mucositis is one of the most common collateral effects in patients undergoing treatment with 5-fluorouracil (5-FU). In this context, It has been previously shown that with only two doses of the protein from the latex fraction of Calotropis procera it was possible to prevent damage caused by 5-FU in the oral mucosa. Thus, the aim of this study was investigate the effect of subfractions of the latex protein (PL) of Calotropis procera in the prevention of oral mucositis induced by 5-FU in hamsters. At first, the subfractions (PI, PII and PIII) of the PL of Calotropis procera were identified by chromatography. Hamsters received 0.9% saline, i.p., (Control) or Mechanical Trauma (TM) or 5-FU (60mg / kg and 40mg / kg, i.p., respectively, on the 1st and 2nd day of the experimental protocol). 24h and 72h after of the last dose of the chemotherapeutic, PL 5mg / kg (PL + 5-FU) or its subfractions were administered: PI 5mg / kg (PI + 5-FU); PII 5mg / kg (PII + 5-FU); PIII 5mg / kg (PIII + 5-FU) and PII IAA 5mg / kg (PII IAA + 5-FU). On the 4th day, all experimental groups, except the control, were submitted to TM. The animals were observed daily until the tenth day of the experimental protocol to evaluate survival and weight loss. Then, the animals were anesthetized and their jugal mucosas were exposed for the mascroscopic analysis. Hamsters were euthanized and their jugal mucosa were collected to evaluate the following parameters: histopathological analysis, neutrophil recruitment (myeloperoxidase dosage, MPO), oxidative stress (GSH and MDA levels), inflammation (levels of TNFα and IL- ELISA, including protein expression of IL-1β, ICAM-1 and Iba-1 by immunohistochemistry) and integrity of collagen fibers (PicroSirius Red staining). From the PL fraction of Calotropis procera, the subfractions PI, PII and PIII were identified and showed to be quite distinct. In addition, PII and PIII showed intense proteolytic activity. The proteolytic activity of PII was inhibited with iodoacetamide, leading to PII IAA. 5-FU reduced survival, caused intense weight loss, caused extensive ulcer formation, development of abscesses, marked erythema, haemorrhage and edema. In addition, it also promoted formation of ulcers, characterized by loss of integrity of the jugal epithelium and intense infiltration of inflammatory cells. In addition, 5-FU increased the levels of MPO, MDA, IL-1β and TNF-α, including the expression of ICAM-1 and Iba-1, as well as decreased GSH levels and reduced collagen fibers in the oral mucosa compared to the control group. Whereas only PL or IAA PII were able to prevent these 5-FU promoted alterations. It is concluded that PII with its proteolytic activity inhibited by IAA is the subfraction responsible for the previously observed beneficial effects of PL on oral mucositis induced by 5-FU. Therefore, PII IAA attenuates 5-FU induced oral mucositis by reducing oxidative stress, inflammation (by decreasing the expression of adhesion molecules, neutrophil recruitment and macrophage activation with consequent decrease of IL-1β and TNF- Α). Thus, it prevents degradation of collagen fibers, including weight loss and increased survival in animals submitted to experimental oral mucositis.